2017
DOI: 10.4168/aair.2017.9.5.446
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nasal Cellulose Powder in the Symptomatic Treatment of Allergic Rhinitis: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: PurposeNasal Cellulose Powder (NCP), which can prevent from binding an allergen to nasal mucosa, may reduce allergic rhinitis (AR) symptoms in dust mite-sensitized children. This study was conducted to assess the efficacy of NCP in improving clinical symptoms of a nasal airflow limitation and the response of nasal inflammatory cells.MethodsChildren with dust mite-sensitized AR aged 6-18 years were recruited. After a 4-week run-in period, NCP or a placebo was administered, 1 puff per nostril 3 times daily for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In contrast, another study demonstrated that CP conferred no significant effect on ameliorating dust mite-sensitized AR children [13]. However, previous studies were limited by the relatively short duration of clinical observations and only patients’ subjective rating being assessed.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, another study demonstrated that CP conferred no significant effect on ameliorating dust mite-sensitized AR children [13]. However, previous studies were limited by the relatively short duration of clinical observations and only patients’ subjective rating being assessed.…”
Section: Introductionmentioning
confidence: 94%
“…Before NPT, participants were asked to discontinue topical nasal corticosteroids for 2 weeks, antihistamine medication for a week, and oral or topical decongestants for a day. NPT protocol was modified using our previous report 10 and a recent study in chidren 11 as follows. Firstly, baseline nasal symptom scores were recorded, then nasal airway resistance (NAR) and nasal airflow patency were assessed using anterior rhinomanometry analyzes (Multifunctional Spirometer HI-801, Chest M.I, Inc., Tokyo, Japan) and peak nasal inspiratory flows (PNIF) (In-Check Nasal, Clement Clark, Harlow, UK).…”
Section: Hdm Nasal Provocation Testmentioning
confidence: 99%
“…Further scientific evidences have become available owing to more recent clinical trials that investigated the efficacy of these products in adults and children (Åberg et al, 2014, 2011). However, contrasting data have been just published following a randomized, double-blind trial in 60 dust mite-sensitized AR children comparing the nasal cellulose powder with placebo (Manuyakorn et al, 2017). The placebo was a lactose powder having the same particle size and appearance as the cellulose powder.…”
Section: Non-pharmacologically Active Substancesmentioning
confidence: 99%